Des émotions professionnelles dans la relation socio-éducative à l’hôpital et dans la police. Une construction collective et individuelle de l’intelligence émotionnelle - Thomas Bonnet (Sociétés et Jeunesses en Difficulté)
Based on a comparative study of hospital pediatric services and two police departments, the article studies the emotions in socio-educational relation. He supports the idea that the work on the feelings realized by the professionals is fundamental in this relationship ; in other words, it is a professional skill. This article shows the shape that this emotional intelligence can set. Besides, he questions the origin of this intelligence by underlining that it is at the same time the result of a collective organization and an individual caree.